Postvaccination SARS-CoV-2 infections among skilled nursing facility residents and staff members — Chicago, Illinois, December 2020–March 2021 - Teran, Richard A. (Am J Transplant, 2021)
This article describes 22 cases of breakthrough SARS-CoV-2 infection among over 14,000 fully vaccinated skilled nursing facility residents and staff. The majority of such infections were asymptomatic or were associated with mild symptoms, and there was no intra- facility spread related to these cases. This report suggests that postvaccination breakthrough infections are rare, but also confirms that vaccines do not offer 100% protection even in nonimmunosuppressed hosts, thus underscoring the need for studies of vaccine efficacy in immunosuppressed transplant recipients.